Conformational flexibility of interdomain linker in bovine tyrosyl-tRNA synthetase studied by molecular dynamics simulation - Pydiura, N.A.; Tereshchenko, F.A.; Kornelyuk, A.I. (Біополімери і клітина, 2006)
Here we report a study of molecular dynamics of a YCD2 fragment of mammalian tyrosyl-tRNA synthethase (Asp322-Ser528), which includes the COOH-terminal cytokine-like domain, intermodular flexible linker, and H5-α-helix of catalytic core of synthetase. Our calculations show that while compact C-terminal domain was less flexible and relatively stable, the interdomain linker shows a high degree of conformational changes. After short relaxation time it forms a short helix-like structure, which may be involved in the regulation of domain interaction and modulation of protein activities. Здійснено дослідження молекулярної динаміки YCD2- фрагмента тирозил-тРНК синтетази ссавців (Asp322-Ser528), який включає СООН-кінцевий цитокінподібньїй модуль, міжмодульний гнучкий лінкер та Н5-α-спіраль каталітичного модуля синтетази. У процесі динаміки компактний С-кінцевий домен виявився менш рухливим і відносно стабільним, тоді як міжмодульний лінкер піддався значним конформаційним перебудовам. Після короткого періоду релаксації у лінкері виявлено формування короткої спіральної ділянки, яка може бути причетною до регуляції взаємодії доменів і модуляції активностей білка. Описано исследование молекулярной динамики фрагмента YCD2 тирозил-тРНК синтетазы млекопитащих (Asp322-Ser528), включающего СООН-концевой цитокинподобный домен, межмодульный гибкий линкер и Н5-α-спираль каталитического модуля синтетазы В процессе динамики компактный С-концевой домен белка оказался менее подвижным и относительно стабильным, тогда как межмодульный линкер выявил значительные конформационные перестройки. После короткого периода релаксации обнаружено образование короткого спирального участка, который может быть вовлечен в регулирование взаимодействия доменов и модуляции активностей белка.